2015
DOI: 10.1016/j.aquaculture.2014.09.044
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stocking density and food deprivation in silver catfish (Rhamdia quelen): A metabolic and endocrine approach

Abstract: The influence of stocking density and food deprivation on energy metabolism, stress processes and the pituitary endocrine system of silver catfish (Rhamdia quelen) was investigated after a period of 14 days, in which plasmatic and hepatic parameters and the mRNA expression of prolactin (PRL), growth hormone (GH) and somatolactin (SL) were assessed. The fish were subjected to four experimental conditions: (1) fed under high stocking density (32 kg/m 3 , HSD); (2) fed under mean stocking density (16 kg/m 3 , MSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 46 publications
7
33
0
2
Order By: Relevance
“…High plasma cortisol levels were observed in the control group, demonstrating that the stocking density and the limited space of the 60 L tanks of the present experiment was stressful for R. quelen as previously indicated by Barcellos et al (2004) and Menezes et al (2015). According to Barcellos et al (2001) .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…High plasma cortisol levels were observed in the control group, demonstrating that the stocking density and the limited space of the 60 L tanks of the present experiment was stressful for R. quelen as previously indicated by Barcellos et al (2004) and Menezes et al (2015). According to Barcellos et al (2001) .…”
Section: Discussionsupporting
confidence: 64%
“…A recent study demonstrated that feeding R. quelen with different levels of dietary EOLA for 60 days does not affect growth, but alters some metabolic parameters and improves the antioxidant status (Saccol et al, 2013). However, it is not known whether the effect of EOLA on anesthesia and antioxidant status may induce any protective effect in R. quelen exposed to non-optimal culture situations, as at a stocking density of 10.6 kg m -3 , which is considered stressful for this species when fish are maintained in a limited space (tanks or cages around up to 300-400 L) (Barcellos et al, 2004;Menezes et al, 2015). Consequently, the aim of this study was to evaluate metabolic, osmoregulatory and endocrinological parameters of R. quelen fed with a diet containing different levels of EOLA and submitted to a stressful situation.…”
Section: Introductionmentioning
confidence: 99%
“…2). In addition, the same kind of cortisol response in specimens held at the lowest stocking density has been recently demonstrated in specimens of the silver catfish (Rhamdia quelen) (Menezes et al, 2015), suggesting that this hormone is also species-dependent regarding the stocking density and the proper nature of the specimens. Moreover, the concordance about the enhancement of plasma cortisol and glucose observed in the LD group, together with the stimulation of hepatic glycogenolytic and glucose export capacity demonstrated in this tissue ( Fig.…”
Section: Tablementioning
confidence: 57%
“…Compared with Cl − and GLU, other serum parameters TG, TCH and TP in salmon were not affected by stocking density in this study, a finding that agrees with other density trials in European sea bass and silver catfish Rhamdia quelen (Di Marco et al . ; Menezes, Ruiz‐Jarabo, Martos‐Sitcha, Toni, Salbego, Becker, Loro, Martínez‐Rodríguez, Mancera & Baldisserotto ).…”
Section: Discussionmentioning
confidence: 99%